The Effect of Locus of Control and Self-Efficacy on the Job Satisfaction of BPJS Kesehatan Banjarmasin Branch Employees - Adesti, Aulia; Prima Jaya, Fanlia; Dewi, Tusiana (PT. Hanken Sukses Jaya, 2025)
This study aims to analyze the influence of Locus of Control and Self-Efficacy on Job Satisfaction among employees of BPJS Kesehatan Banjarmasin Branch. The background of this research is the phenomenon of low employee job satisfaction, as reflected in complaints about workload, service-target pressure, and a lack of enthusiasm. The study focuses on the importance of individual psychological factors in maintaining job satisfaction amid public policy dynamics and the complexity of healthcare services. The population consists of all employees of the BPJS Kesehatan Banjarmasin Branch, and 81 respondents were selected using saturated sampling. Data were collected through questionnaires using a Likert scale and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, and F-tests, with the assistance of SPSS software. The results indicate that Locus of Control has a significant effect on employee job satisfaction. Self-efficacy also significantly affects employee job satisfaction. Simultaneously, both independent variables significantly affect employee job satisfaction. These findings suggest that the better the employees’ Locus of Control and Self-Efficacy, the higher their level of job satisfaction.